The basic preconditions for economic education in schools majoring in technology - Кулішов, Володимир (Pedagogy of Higher and Secondary Education, 2014)
Kulishov V. S. The basic preconditions for economic education in schools majoring in technology. The article highlights the basic preconditions as well as substantiates the great importance of creating the system of economic education in schools majoring in technology.